Standard specifications for transportation materials and methods of sampling and testing and AASHTO provisional standards (American Association of State Highway and Transportation Officials, 2015)
The five-volume Materials Book and Provisional Standards set contains 479 specifications, test methods, and provisional standards -- including 71 revised and 19 new -- commonly used in the construction of highway facilities. 2015. 4,652 pp, 5 volumes.